Разработка и апробация пластикового болюса для гамма терапии - Сорокина А. А. Аида Арсеновна; Булавская А. А. Ангелина Александровна; Бушмина Е. А. Елизавета Алексеевна; Милойчикова И. А. Ирина Алексеевна (2022, 2022)
Заглавие с экрана